2007
DOI: 10.1165/rcmb.2006-0418oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Hyperresponsiveness, Remodeling, and Smooth Muscle Mass

Abstract: We quantified the effects of airway wall remodeling upon airway smooth muscle (ASM) shortening. Isolated ASM from sheep was attached to a servo-controller that applied a physiologic load. This load could be altered to reflect specified changes of airway wall geometry, elasticity, parenchymal tethering, transpulmonary pressure (P L ), and fluctuations in P L associated with breathing. Starting at a reference length (L ref ), ASM was stimulated with acetlycholine and held at constant P L of 4 cm H 2 O for 2 h. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 48 publications
6
105
0
Order By: Relevance
“…These reversible or partially irreversible modifications alter the composition of the airway wall, contributing to luminal diameter narrowing in asthma (13,45). Furthermore, studies suggest that alterations in airway structural cell size or accumulation can influence AHR (46,47). In this section, we identify mechanisms underlying the fibrosis, differentiation, proliferation, and apoptosis involved in TGF-b1-induced airway structural cell remodeling.…”
Section: Airway Remodeling and Proliferationmentioning
confidence: 99%
“…These reversible or partially irreversible modifications alter the composition of the airway wall, contributing to luminal diameter narrowing in asthma (13,45). Furthermore, studies suggest that alterations in airway structural cell size or accumulation can influence AHR (46,47). In this section, we identify mechanisms underlying the fibrosis, differentiation, proliferation, and apoptosis involved in TGF-b1-induced airway structural cell remodeling.…”
Section: Airway Remodeling and Proliferationmentioning
confidence: 99%
“…Findings obtained thus far with a hybrid approach of a freshly dissected airway smooth muscle and a virtual human asthmatic airway have reinforced the long-held conclusion that the functionally dominant derangement accounting for airway hyperresponsiveness is increased smooth muscle mass [21,38]. The main mechanisms underlying airway hyperresponsiveness, however, are intrinsically dynamic, and are therefore unaccounted for in previous theoretical models, which are intrinsically static.…”
Section: Model Translation To Humansmentioning
confidence: 84%
“…Recently, Oliver et al used the same hybrid approach to study the sensitivity of muscle length to changes of tidal volume, muscle activation, and thickening of airway wall compartments [38]. They found that smooth muscle mass is the functionally dominant cause for excessive airway narrowing (Fig.…”
Section: Behavior Of Airway Smooth Muscle Under Physiologic Loading Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these length oscillations are known to decrease ASM stiffness, even during supra-maximal activation with ACh (66,84,128,198). Importantly, the maximal force-generating capacity of ASM during or immediately following these oscillations is also reduced (66,84,85,128,186,198,242). The decline in isometric force that ensues length oscillations has been shown to be proportional to the amplitude and the duration of the stretch, but not to the frequency (242).…”
Section: Muscle Factorsmentioning
confidence: 99%